THE BENEFITS OF STRENGTH TRAINING IN IMPROVING THE QUALITY OF LIFE OF ELDERLY PEOPLE - Clayton Aves dos Santos, Anderson; Lucena de Andrade, Gilvaney; Adegilson da Silva Barbosa, Antonio (Health and Society, 2021)
One of the characteristics of aging is the structural functional decline of cells and tissues in all organs. Aging does not start suddenly at age 60, but it consists in the accumulation and interaction of social, medical and behavioral processes throughout life, when the progressive decline of several physiological changes occurs, decrease in muscle and bone mass are the main contributors to the decline in the independence and quality of life of the elderly. Studies report that strength training is one of the best exercises for strength gain in the elderly, this method is a way to reduce declines in strength and muscle mass, resulting in improved health and quality of life.